Performance management system in the higher learning institutions in Tanzania: horses for courses? - Thobias Komungemwe; Ramadhani Marijani (Cogent Education)
Using the University of Dodoma and the College of Business Education, this study examined the performance Management System process in higher learning institutions in Tanzania. To achieve this objective, we employed a two-case mixed approach with a sample size of 256 respondents and 12 Key informants. This allowed us to study organizational context, in-depth issues, and the meaning of performance management using the Performance Improvement Model (PIM). The findings report compliance with the PIM, the PMS success factors, the challenges of implementing PMS in HLIs in Tanzania, and the context-specific factors for implementing performance management. Lastly, conclusions, recommendations, and emerging new research themes are identified.